A novel Ni–WC/AC catalyst with enhanced electroactivity for glucose oxidation. Issue 9 (7th March 2015) - Qi, Suitao; Yue, Jiaqi; Hao, Chen; Li, Yingying; Yi, Chunhai; Yang, Bolun
<x xml:space="preserve">Abstract</x> A novel Ni–WC/AC catalyst possessed enhanced electroactivity for glucose oxidation due to the synergistic effect between Ni and WC.